The negative compatibility effect with relevant masks: a case for automatic motor inhibition - Ocampo, Brenda; Finkbeiner, Matthew (Frontiers in Psychology, 2013)
For many years controversy has surrounded the so-called “negative compatibility effect” (NCE), a surprising phenomenon whereby responses to a target stimulus are delayed when the target is preceded by an unconscious, response-compatible prime. According to proponents of the “self-inhibition” hypothesis, the NCE occurs when a low-level self-inhibitory mechanism supresses early motor activations that are no longer supported by perceptual evidence. This account has been debated, however, by those who regard the NCE to be a stimulus-specific phenomenon that can be explained without recourse to a self-inhibitory mechanism. The present study used a novel reach-to-touch paradigm to test whether unconscious response priming would manifest as motor activation of the opposite-to-prime response (supporting mask-induced priming accounts), or motor inhibition of the primed response (supporting the notion of low-level self-inhibition). This paper presents new findings that show the emergence of positive and negative compatibility effects as they occur in stimulus processing time. In addition, evidence is provided suggesting that the NCE is not driven by the activation of the incorrect, “opposite-to-prime” response, but rather might reflect automatic motor inhibition.